Role of Aryl Hydrocarbon Receptor in Circadian Clock Disruption and Metabolic Dysfunction - Cassie Jaeger; Shelley A. Tischkau (SAGE Publishing, 2016)
The prevalence of metabolic syndrome, a clustering of three or more risk factors that include abdominal obesity, increased blood pressure, and high levels of glucose, triglycerides, and high-density lipoproteins, has reached dangerous and costly levels worldwide. Increases in morbidity and mortality result from a combination of factors that promote altered glucose metabolism, insulin resistance, and metabolic dysfunction. Although diet and exercise are commonly touted as important determinants in the development of metabolic dysfunction, other environmental factors, including circadian clock disruption and activation of the aryl hydrocarbon receptor (AhR) by dietary or other environmental sources, must also be considered. AhR binds a range of ligands, which prompts protein-protein interactions with other Per-Arnt-Sim (PAS)-domain-containing proteins and subsequent transcriptional activity. This review focuses on the reciprocal crosstalk between the activated AhR and the molecular circadian clock. AhR exhibits a rhythmic expression and time-dependent sensitivity to activation by AhR agonists. Conversely, AhR activation influences the amplitude and phase of expression of circadian clock genes, hormones, and the behavioral responses of the clock system to changes in environmental illumination. Both the clock and AhR status and activation play significant and underappreciated roles in metabolic homeostasis. This review highlights the state of knowledge regarding how AhR may act together with the circadian clock to influence energy metabolism. Understanding the variety of AhR-dependent mechanisms, including its interactions with the circadian timing system that promote metabolic dysfunction, reveals new targets of interest for maintenance of healthy metabolism.